Secondary Squamous Cell Carcinoma of the Tongue Complicated with Bronchiolitis Obliterans as a Manifestation of Graft-versus-Host Disease following Peripheral Blood Stem Cell Transplantation - Kengo Hashimoto; Toru Nagao; Shin Koie; Satoru Miyabe; Terumi Saito (Case Reports in Hematology)
Peripheral blood stem cell transplantation (PBSCT) has increasingly been used for hematologic cancer therapy, resulting in improved survival rates. However, risks include graft-versus-host disease (GVHD) and secondary solid tumors. Here, we describe a case of tongue squamous cell carcinoma (SCC) complicated by bronchiolitis obliterans (BO) following PBSCT. A 42-year-old man with a history of acute lymphocytic leukemia treated with PBSCT presented with multiple white lesions and erosions on the tongue and buccal mucosa that are compatible with oral chronic GVHD (NIH criteria: score 2). The lesions were presented for 8 years. The patient had a history of BO manifested as GVHD. During follow-up, an exophytic mass was rapidly developed on the left dorsum of the tongue. Biopsy of this lesion confirmed SCC (cT2N0M0). Pulmonary function testing for general anesthesia was almost normal. Hemiglossectomy, supraomohyoid neck dissection, and tongue reconstruction were performed. Thirteen months after surgery, the patient showed neither recurrence of tumor nor progression of oral GVHD. However, the patient died of respiratory failure due to repeated pneumothoraxes and deterioration of BO.